Applied mechanics and materials III selected, peer reviewed papers from the 2014 3rd International Conference on Applied Mechanics and Materials (ICAMM 2014), November 15-16, 2014, Shenzhen, China - Choi, Seung-Bok; Kim, Yun-Hae (Applied mechanics and materials ;, 2015)
Collection of selected, peer reviewed papers from the 2014 3 rd International Conference on Applied Mechanics and Materials (ICAMM 2014), November 15-16, 2014, Shenzhen, China. The 191 papers are grouped as follows: Chapter 1: Solid Mechanics and its Applications; Chapter 2: Fluid Mechanics and its Applications; Chapter 3: Computational Mechanics and its Applications; Chapter 4: Mechanics of Explosion and Technologies of Blasting; Chapter 5: Structural Mechanics, Geotechnical Mechanics and Infrastructure Construction; Chapter 6: Building Materials;Chapter 7: Composites;Chapter 8: Micro/Nano Ma.